Mobile phone use for a social strategy to improve antiretroviral refill experience at a low-resource HIV clinic: patient responses from Nigeria. Issue 5 (4th May 2017) - Adetunji, Adedotun A.; Muyibi, Sufiyan A.; Imhansoloeva, Martins; Ibraheem, Olusola M.; Sunmola, Adegbenga; Kolawole, Olubunmi O.; Akinrinsola, Oluwasina O.; Ojo-Osagie, James O.; Mosuro, Olusola A.; Abiolu, Josephine O.; Irabor, Achiaka E.; Okonkwo, Prosper; et al.
ABSTRACT: In sub-Saharan African areas where antiretroviral (ARV) drugs are not available through community pharmacies, clinic-based pharmacies are often the primary source of ARV drug refills. Social pressure is mounting on treatment providers to adjust ARV refill services towards user-friendly approaches which prioritize patients' convenience and engage their resourcefulness. By this demand, patients may be signalling dissatisfaction with the current provider-led model of monthly visits to facility-based pharmacies for ARV refill. Mobile phones are increasingly popular in sub-Saharan Africa, and have been used to support ARV treatment goals in this setting. A patient-centred response to on-going social pressure requires treatment providers to view ARV refill activities through the eyes of patients who are negotiating the challenges of day-to-day life while contemplating their next refill appointment. Using focus groups of five categories of adult patients receiving combination ARV therapy, we conducted this cross-sectional qualitative study to provide insight into modifiable gaps between patients' expectations and experiences of the use of mobile phones in facility-based ARV refill service at a public HIV clinic in Nigeria. A notable finding was patients' preference for harnessing informal social support (through intermediaries with mobile phones) to maintain adherence to ARV refill appointments when they could not present in person. This evolving social support strategy also has the potential to enhance defaulter tracking. Our study findings may inform the development of ARV refill strategies and the design of future qualitative studies on client–provider communication by mobile phones in under-resourced HIV treatment programmes.